Music Analysis Experience: New perspectives in musical semiotics - Maeder, Costantino; Reybrouck, Mark (Leuven Leuven University Press, 2015)
Transdisciplinary and intermedial analysis of the experience of music. Nowadays musical semiotics no longer ignores the fundamental challenges raised by cognitive sciences, ethology, or linguistics. Creation, action and experience play an increasing role in how we understand music, a sounding structure impinging upon our body, our mind, and the world we live in. Not discarding music as a closed system, an integral experience of music demands a transdisciplinary dialogue with other domains as well. Music, Analysis, Experience brings together contributions by semioticians, performers, and scholars from cognitive sciences, philosophy, and cultural studies, and deals with these fundamental questionings. Transdisciplinary and intermedial approaches to music meet musicologically oriented contributions to classical music, pop music, South American song, opera, narratology, and philosophy.